GLULAM BEAMS WITH HOLES (Advances in Civil and Architectural Engineering, 2021)
This paper provides a systematic review of research on glued laminated timber beams with circular and rectangular openings. Experiments on girders with unreinforced openings varied several parameters, including the girder span and shape, opening position and shape, and the relationship between the stress state near the opening and the ratio of opening size to girder size. We compare experimental results with recommendations given by DIN 1052:2004-08, DIN EN 1995-1-1/NA: 2010, prEN 1995-1-1: Final Draft, analytical expressions, and other relevant standards, as well as with the results of numerical models using the finite element method. Because of its myriad complexities and uncertainties, this area remains open for further research and for implementation of that research into practical design guidelines and rules.